Dartfish Sebagai Alat Ukur Perkembangan Motorik Anak Usia Pendidikan Dasar - Soetjipto, (Pendidikan Sekolah Dasar, 2009)
The aims of this study  are: (1). Introducing how to use Dartfish program on measuring skill development, (2). Measuring  the quantitatively  child  motor learning development on short serve on playing badminton.  (3). Find out the level of skill on short serve, of the badminton players, of 10-13th years old . Nine amateur badminton players were filmed before and after feedback to find out the level of skill motor learning development on short serve. The short serve was analyzed because of its importance to success in badminton. Each subject was filmed at 50 frames per second hitting 5 short serves. Feedback was given three times in a week and treated directly. The difference treatment for the experimental group (B group) badmintons players, was invited to have discussion and suggestion by either coach or researcher based on note and coach also researcher observation by naked eye, but the second experimental (C group) to have discussion and suggestion by either coach or researcher based on note and coach also researcher observation by using recording (nonconventional feedback). The results showed that the badminton players The result shows that their skill development of the badminton players on short serve are still low, although they have been train 3 times a week on technique exercise.